Colorectal surveillance outcomes from an institutional longitudinal cohort of lynch syndrome carriers - del Carmen, Gabriel; Reyes-Uribe, Laura; Goyco, Daniel; Evans, Kyera; Bowen, Charles M.; Kinnison, Jennifer L.; Sepeda, Valerie O.; Weber, Diane M.; Moskowitz, Julie; Mork, Maureen E.; Thirumurthi, Selvi; Lynch, Patrick M.; et al. (Frontiers in Oncology, 2023)
Objective:Lynch Syndrome (LS) carriers have a significantly increased risk of developing colorectal cancer (CRC) during their lifetimes. Further stratification of this patient population may help in identifying additional risk factors that predispose to colorectal carcinogenesis. In most LS patients CRC may arise from adenomas, although an alternative non-polypoid carcinogenesis pathway has been proposed for PMS2 carriers. Using data from our institutional LS cohort, our aim was to describe our current colorectal screening outcomes with a focus on the incidence of adenomas in the context of different MMR genotypes and patient demographics such as gender, race, and ethnicity.Design: We collected demographics, genetic, colonoscopy, and pathology results from a total of 163 LS carriers who obtained regular screening care at MD Anderson Cancer Center. Data were extracted from the electronic health records into a REDCap database for analysis. Logistic regressions were performed to measure the association between MMR variants and the likelihood of adenomas, advanced adenomas, and CRC. Then, we analyzed the cumulative incidences of these outcomes for the first 36 months following enrollment using Kaplan-Meier incidence curves, and Cox proportional hazard regressions.Results:On multivariate analysis, age (≥45 years old) was associated with an increased risk of developing adenomas (P=0.034). Patients with a prior or active cancer status were less likely to develop adenomas (P=0.015), despite of the lack of association between surgical history with this outcome (P=0.868). We found no statistically significant difference in likelihood of adenoma development between MLH1 and MSH2/EPCAM, MSH6, and PMS2 carriers. Moreover, we observed no statistically significant difference in the likelihood of advanced adenomas or CRC for any measured covariates. On Cox proportional hazard, compared to MLH1 carriers, the incidence of adenomas was highest among MSH2/EPCAM carriers during for the first 36-months of follow-up(P<0.001). We observed a non-statistically significant trend for Hispanics having a higher and earlier cumulative incidence of adenomas compared to non-Hispanics(P=0.073). No MMR carrier was more likely to develop advanced adenomas. No difference in the incidence of CRC by MMR gene(P=0.198). Conclusions:Screening recommendations for CRC in LS patients should be based on specific MMR variants and should also be tailored to consider patient demographics.